Involvement in Crime and Delinquency and the Development of Technological and Computer Skills: A Longitudinal Analysis - Rima, Dzhansarayeva (International journal of offender therapy and comparative criminology, 2023)
A body of research has revealed that involvement in crime and delinquency is associated with a wide number of social, economic, and health consequences. The current study built off this knowledge base and examined whether measures of adolescent violent delinquency and contact with the criminal justice system were related to the access of basic, and experience with, technology, and computers. To do so, longitudinal data drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health) were analyzed. The results revealed that self-reported violent delinquency in adolescence was associated with a decreased probability of owning a computer and having an email account 10 to 12 years into the future. Additionally, measures of contact with the criminal justice system, low self-control, delinquent peers, and governmental public assistance were also associated with the probability of owning a computer and having an email account.